Model Pengembangan Pelayanan Desa Terintegrasi (Studi pada Kabupaten Banyuwangi dan Bondowoso Provinsi Jawa Timur) - Nian Riawati (Trunojoyo University of Madura, 2020)
This study describes the practice of E-Government in the regions through the Smart Village Program in Banyuwangi district and the Village Information Administration System (SAID) Program in the Bondowoso district. By using descriptive qualitative research methods, this study can describe the context and set it naturally. The results showed that the smart village program in Banyuwangi District and the SAID Program in Bondowoso District could realize independent villages in data and information and could improve the quality of services to the community for the better. The town has a database that used as a reference for the district government in making empowerment policies and making services to the city faster, easier, and cheaper. There are some problems in its implementation, such as remote villages that do not yet have an internet network, the low competence of human resources in the town, the weak support from the village government, and the lack of facilities and infrastructure.